Indirect management of regional public television in Spain: Study of the channel model (2012-2018) - Andúgar,Isabel Sarabia (2020)
Since 2012, Spanish legislation has authorized the regional governments to choose their own model of management for their regional television channels. This freedom to decide has allowed the creation of a new, unprecedented television model, namely indirectly-managed regional public service, based on outsourcing content creation. This new modality has been adopted by the Autonomous Community of the Region of Murcia, which is the first government to develop an initiative of this nature. This article proposes, on the one hand, to study the regulatory reform of regional public television in Spain, and on the other, to analyze how this reform has affected the creation of the management model used for the regional public television, 7RM. The academic work on this topic is scarce. The research methods used are mainly an analysis of legal and official documents, which are specifically supported by bibliographic sources related to the subject matter.